Androgen and prolactin manipulation do not induce changes in immunocompetence measures in a fish with male parental care. Issue 3 (23rd December 2022) - Cunha, Adriano A. P.; Garner, Shawn R.; Ingoldsby, Erin; Dixon, Brian; MacDougall‐Shackleton, Scott A.; Knapp, Rosemary; Neff, Bryan D.
Abstract: Prolactin and 11‐ketotestosterone (11‐KT) are important reproductive hormones in fishes, which may also influence immunocompetence. The immunocompetence handicap hypothesis states that higher androgen concentrations that support secondary sex traits are traded off against a decrease in immune system function. To test the relationships between these hormones and immunocompetence, we experimentally manipulated 11‐ketotestosterone and prolactin in the freshwater fish, bluegill ( Lepomis macrochirus ) during parental care using implants that contained either 11‐KT, prolactin, or an inert control. We vaccinated individuals to stimulate the acquired immune response, then measured immunocompetence as the number of granulocytes, lymphocytes and monocytes, and the expression of interleukin 8 in each sample. We did not observe any significant differences in the immune measures among the hormone treatments. Our results indicate that in bluegill, there is no trade‐off between androgens or prolactin and immunocompetence. Abstract : Androgen and prolactin did not changes in immune response to a vaccine. Research Highlights: Prolactin or androgen (11‐KT) treatment did not affect immune responses in bluegill sunfish. We find no support the immunocompetence handicap hypothesis in fish. Increased 11‐KT affected behavior, but not the immune response to a vaccine.